Clinical observation of monoclonal fibrillary glomerulonephritis - T. A. Garkusha; F. V. Alyab'ev; T. A. Vdovik (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Monoclonal gammopathy of renal significance is a condition caused by the proliferation of a clone of B-lymphocytes or plasma cells that does not reach the criteria required for the initiation of treatment for oncohematological indications, but is characterized by the secretion of nephrotoxic paraprotein. There are many morphological variants of this disease and their diagnosis requires the use of additional research methods. This article presents a clinical observation of a 54-year-old patient admitted to the nephrology department with nephrotic syndrome. According to the results of nephrobiopsy, the patient was diagnosed with monoclonal fibrillary glomerulonephritis. Additional examination of the patient did not reveal signs of lymphoproliferative disease.